2011
DOI: 10.1097/ico.0b013e3181e2ba61
|View full text |Cite
|
Sign up to set email alerts
|

Biometric Evaluation of Keratoconic Eyes With Slit Lamp–Adapted Optical Coherence Tomography

Abstract: This study provides further validation that anterior segment optical coherence tomography is a reliable method to assess important parameters for diagnosis and therapeutic outcome control of patients with keratoconus. This method may be particularly useful as a safe and well-defined preoperative diagnostic tool before keratoplasty or corneal cross-linking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…The Orbscan requires a clear reflection from the epithelial and endothelial surfaces as well as a homogeneous composition of the optical media to obtain precise measurements [21,32]. No difficulty was observed making the measurements in the current study with the Orbscan in KC subjects, which is in line with the findings of Aurich et al [51]. However, with the Orbscan corneal angle estimation tool, the clinician subjectively identifies the apex of the anterior chamber angle and aligns a line tangential to the posterior surface of the cornea and the anterior surface of the iris.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The Orbscan requires a clear reflection from the epithelial and endothelial surfaces as well as a homogeneous composition of the optical media to obtain precise measurements [21,32]. No difficulty was observed making the measurements in the current study with the Orbscan in KC subjects, which is in line with the findings of Aurich et al [51]. However, with the Orbscan corneal angle estimation tool, the clinician subjectively identifies the apex of the anterior chamber angle and aligns a line tangential to the posterior surface of the cornea and the anterior surface of the iris.…”
Section: Discussionsupporting
confidence: 90%
“…Aurich et al [51] has shown that anterior segment OCT is a reliable method to assess important parameters for diagnosis and therapeutic outcomes of patients with keratoconus. The use of OCT techniques for corneal biometric evaluation has also become more common and is likely to be used alongside or substituted for more traditional measurements based on, for example, ultrasound and Orbscan techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Eyes with deeper Descemet membrane detachments and larger Descemet membrane breaks require more time for resolution of corneal edema despite intracameral gas injection [25]. Aurich et al [27] demonstrated that in intrastromal cysts, there is an area of hyporeflectivity within the corneal stromal bed on slit lamp adapted optical coherence tomography.…”
Section: Anterior Segment Optical Coherence Tomographymentioning
confidence: 99%
“…6 It has been shown that KC patients have deeper anterior chamber than that of normal population and a few publications showed that axial length was also higher in keratoconic eyes. [7][8][9][10] Vernal keratoconjunctivitis (VKC) is a chronic allergic inflammation of ocular surface involving eosinophil, mast cell, CD4 T cell, B cell, and NK cell. 11,12 The local cytokine profile of VKC patients are paradoxical mixture of Th0, Th1, and dominant Th2, indicating the role of NKT cells.…”
Section: Introductionmentioning
confidence: 99%